The Effect of Throttle Signal Output Voltage Variation and Load on Current Consumption - Dwi Rangga Wardana, Sahwala; Amalia, Zakiyah (International Journal of Frontier Technology and Engineering, 2024)
Many electric motorcycle users complain about the difficulty in controlling acceleration with precision, especially if they have never ridden a motorized vehicle before. This control difficulty is a result of the characteristics of BLDC motors, which have high torque instantly. While this characteristic is generally considered an advantage, in this discussion it is a disadvantage that can reduce rider comfort when operating an electric motorcycle. When the rider twists the throttle for the first time, the electric motor immediately spins at maximum power. The issues mentioned serve as the background for the this research entitled "The Effect of Throttle Signal Output Voltage Variations and Load on Current Consumption and BLDC Motor Speed in Electric Motorcycles."The method used in this research is an experimental method by varying the load at 60 kg, 70 kg, and 80 kg and three levels of throttle output voltage changes.The results of this study show that changes in load and throttle output voltage affect current consumption and BLDC motor speed. The highest current consumption is achieved when the vehicle is loaded with 80 kg and using mode 1 at 3.5309 A. The lowest current consumption is achieved when the vehicle is loaded with 60 kg and using mode 3 at 1.4403 A. The highest rotational speed is obtained in mode 1 with a 60 kg load at 219.341 rpm. The lowest rotational speed is obtained in mode 3 with an 80 kg load at 141.37 rpm.